A demographic exploration of implicit racial bias and perceptions among faculty and students in a California community college - Black, Amber (My University, 2025)
This study explored implicit racial bias in a community college setting by examining whether racial identity and perceptions about racial bias among faculty and students intersect. The researcher examined one Hispanic-serving institution (HSI) as literature suggested a need for data from this demographic. This quantitative study included qualitative data addressing two research questions: What significant associations exist between the racial identification of faculty and that of their students in relation to final grading outcomes? How do faculty and student perceptions regarding faculty racial bias toward students differ? The Pygmalion effect and critical race theory (CRT) were the guiding frameworks that directed this research. CRT and the Pygmalion effect provided lenses through which this study’s research questions and methodology were constructed, and how data collection, findings, and analyses were discussed. These theories addressed unconscious and racial biases related to teachers’ and students’ perceptions. The main findings revealed students perceived less implicit racial bias, microaggressions, and racism than faculty, but full-time faculty perceived more of the former than part-time faculty did. Non-White faculty and White students reported more perceived issues with race than White faculty and non-White students. Faculty and students reported possible anti-White sentiments on campus, and the majority of faculty participants shared they had never taken an implicit racial bias test. These conclusions reveal as higher education institutions continue developing antiracist policies, faculty must continually strive to better understand other faculty, their students, and how diverse needs could best be met. Keywords: Race, racial identification, implicit racial bias, grading outcomes, pygmalion effect, Hispanic serving institution, faculty, students, perceptions, critical race theory (CRT)
Keywords: Race; Implicit racial bias; Hispanic serving institution; Perceptions; Critical race theory; Grading outcomes